Hubungan Pengetahuan dan Dukungan Keluarga dengan Perawatan Pasien TB Paru Rawat Jalan - Selasa, Pius; Aty, Yoany Maria V.B.; Benu, Beatrice Amelia; Nurwela, Trivonia Sri; Romana, Aben B.Y.; Kusmiyati, Kusmiyati; Muhtar, Muhtar (Bima Nursing Journal, 2024)
Backgroound : The importance of knowledge and family support of outpatient pulmonary TB patiens during treatment as part of the disease healing process.The purpose: This study aims to determine the relatonship between knowledge and family support with outpaient care of pulmonary TB patients. The study: The research design in this study is a quantitative method using a Cross Sectional design, the sample in this study were outpatient pulmonary TB patients at the Oesapa Health Center, Kupang City totaling 50 people who were obtained by simple random sampling technique according to the inclusion and exclusion criteria. The Results: The results showed that most of the knowledgee of respondents with pulmonary TB at the Oesapa Health Center in Kupang City was in the good category, namely 42 respndent (84,0%), family support was in the good category, namely 42 respondents (84,0 %) and most of them carried out pulmonary TB treatment. The good ones are 39 respondents (78,0%). The conclusion: There is significant relationship between knowledge and family support with pulmonary TB care with a p value= 0,00< 0,05 and family support with a p value of 0,03 < 0,05. Suggestions: The importance of maintaining the level of knowledge and support of the patient’s family to remain good and for the level knowledge and support of the family that is lacking so that i can be increased by providing information about pulmonary TB.